Exploring Rural Economic Potential through Community-Based Entrepreneurship: Lessons from the Concept of Rural Entrepreneurship - Agus Yulistiyono; Dyah Ayu Suryaningrum; Zulaekah (West Science Journal Economic and Entrepreneurship, 2023)
This research delves into the exploration of rural economic potential through the lens of community-based entrepreneurship in West Java. The study aims to unravel the role of grassroots initiatives in propelling economic growth, job creation, and sustainable development within these regions. Employing a mixed-methods approach, the research amalgamates qualitative interviews and quantitative surveys to holistically collect and analyze data. The research sample encompasses rural entrepreneurs, community leaders, local residents, and relevant government officials. The findings are anticipated to contribute insights into the dynamics of community-based entrepreneurship in rural West Java, providing recommendations for policymakers, development agencies, and local communities on fostering economic growth and sustainable development.